All Days 2006
DOI: 10.2118/97982-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Aphron Drilling Fluids

Abstract: Aphron drilling fluids are being used globally to drill through depleted reservoirs and other under-pressured zones. The primary features of these fluids are their unique low-shear rheology and aphrons (specially designed pressure-resistant microbubbles of air). However, how aphron drilling fluids work is not well understood, which limits acceptance of this technology, along with efforts to optimize the system's performance. Recently a study was undertaken under the auspices of the U.S. Department of Energy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Aphrons form a major part of the drilling fluid at atmospheric pressure (usually 10-15 vol%) (Growcock et al 2006). Concentration of aphrons in drilling fluid is controlled through the surfactant and polymer concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphrons form a major part of the drilling fluid at atmospheric pressure (usually 10-15 vol%) (Growcock et al 2006). Concentration of aphrons in drilling fluid is controlled through the surfactant and polymer concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of aphrons in drilling fluid is controlled through the surfactant and polymer concentrations. At downhole pressures, aphrons form an insignificant volume, e.g., a mud sample containing 12 vol% nitrogen at atmospheric pressure will contain less than 0.06 vol% nitrogen at 3000 psig (Growcock et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The velocities of invading fluids tend to slow as a consequence of radial flow around the wellbore and the bridging action of the CGA bubbles. This causes their shear rates to decrease and viscosities to rise [73].…”
Section: Rheology Of the Prepared Gca-based Fluidsmentioning
confidence: 99%
“…It is reported that the aphrons can survive exposure to elevated pressures much better than conventional bubbles, and can survive compression to at least 27.7 MPa. Also, the volume of aphron can recover nearly 90 % during depressurization (Berkin et al 2005;Ivan et al 2002;Wang et al 2007;White et al 2003;Growcock et al 2006).…”
Section: Effects Of Pressure On the Rheological Propertiesmentioning
confidence: 99%